Energy efficiency decision-making in non-energy intensive industries: content and social network analysis - Jonatas Campos Martins; Maria Isabel Wolf Motta Morandi; Daniel Pacheco Lacerda; Barbara Pisoni Bender Andrade (Production)
Abstract Paper aims The present study aims to identify the limitations of the artifacts used in the decision-making process in the adoption of energy efficiency measures in productive systems, using non-intensive energy companies as a delimitation. Originality Identifies authors and connections, the relationships between them and how these interactions contribute to the advancement of knowledge on the subject. Regarding energy efficiency, studies show that the real investment in initiatives in the industrial sector is below the full potential and that the artifacts used in the decision-making process have severe limitations when used in a complex and dynamic context. Research method In this paper a systematic literature review was conducted from the Literature-Grounded Theory. Additionally, social network analysis was used. Main findings It concludes that the approaches are limited to technical and financial factors and does not consider a systemic and dynamic understanding of different internal and external variables to the organization. Implications for theory and practice The contribution of this study is that it identifies the initiatives that help in the process of decision-making for the adoption of energy efficiency measures in productive systems. Specifically, the focus of this study is on non-intensive energy companies. Scientific articles published in the main databases of management were selected.